THE ARCHITECTURE OF PESANTREN: CURRENT ISSUES, CHALLENGES AND PROSPECT FOR DESIGN FRAMEWORK - Nensi Golda Yuli; Ilya Fadjar Maharika; Frank Eckardt (Journal of Islamic Architecture, 2023)
Pesantren (Islamic Boarding School) is an indigenous educational institution originally from Indonesia and perhaps a unique form of the traditional Islamic education system and spreading to Southeast Asia that neighbouring countries. However, studies on pesantren rarely address physical elements and architecture. Learning pesantren architecture challenges us with representation: definition, how to visualize its form and program, and the design. Finding a body of knowledge on pesantren to excavate "architectural features" is important to study its prospect in architectural terms. This paper attempts to analyze pesantren from the architectural perspective, focusing on the specific feature and finding its current issues, challenges, and prospects for the design framework. Two combination research methods were used: Systematic literature review and case study. A systematic literature review was conducted in the first stage to map the distinctive spatial quality of pesantren. In the second stage, three case studies were conducted to report and analyze the current issues, challenges, and prospects for the design framework. The research shows that the variety of physical conditions is the main current issue of pesantren. The main challenge is the shortage of financial availability while the spatial need to cater to population and development is more increasing. Those conflicting narratives open local responses through incremental design processes in which contextual design frameworks are needed.